Enhancing Information Technology and Professional Communication Competencies for Students of SMKN 3 Maumere in Preparation for Entering the Workforce - Agustinus Lambertus Suban; Alfian Harbiyanto; Maria Florentina Rumba; Yohanes Brekmans M. Darkel (PT. Anagata Sembagi Education, 2025)
The Community Service Program (PkM) at SMK Negeri 3 Maumere aimed to improve students’ information technology skills, digital design abilities, professional communication, and job readiness through practice-based training. The program was designed to equip vocational students with relevant digital and soft skills aligned with current workforce needs. Training materials included Microsoft Office, digital design using Canva, video editing with CapCut, public speaking, professional document writing, interview simulations, and the development of digital portfolios. Evaluation results showed a significant improvement in students’ competencies following the program. The public speaking training achieved an average questionnaire score of 4.65 out of 5, categorized as “Very Good,” indicating a high level of participant satisfaction and skill development. Meanwhile, the Canva and CapCut training obtained an average score of 3.58 out of 4, categorized as “Good to Very Good.” Qualitatively, students demonstrated increased confidence, creativity, and technical ability in producing digital curricula vitae, posters, and video portfolios suitable for internships and job applications. Overall, the program was highly relevant to the needs of SMK Negeri 3 Maumere and provided a tangible contribution to strengthening students’ digital competencies and vocational job readiness.